Peripheral corneal ulcers associated with use of African traditional eye medicines. - Lewallen, S (1995)
The most common cause of monocular blindness in Africa is corneal opacification. Traditional eye medicines (TEM) are widely used in Africa and their use has been associated with corneal ulceration, however, no controlled studies of the effects of TEM on the cornea have been published. We conducted a case-control study of 39 patients with corneal ulcers matched to controls with severe conjunctivitis. Microbiological investigations were conducted on 20 cases. There was a significant association between corneal ulceration and TEM use and, in particular, peripheral corneal ulcerations were significantly associated with TEM use.